Informal unpaid primary caregivers: Who takes care of disabled children, adults and seniors? Cuidadores principales informales no remunerados: ¿quiénes cuidan a niños, adultos y adultos mayores en situación de discapacidad? - Yelincic, A.; Cárcamo, R.A. (My University, 2021)
Introduction: The aim of this study is to characterize informal unpaid primary caregivers of disabled people in a state of dependency regarding the age group they belong to. Material and methods: This was a quantitative, descriptive, correlational, no experimental and comparison group study. The sample consisted of 936 informal caregivers who work in the Region of Magallanes and Chilean Antarctica and whose data was collected from the database of the Cruz del Sur Physical Rehabilitation Center. Results: The main results show that disabled children are primarily taken care by their mothers; unlike adults and older adults that are mainly cared by their couples. Children caregivers are noticeably younger than adult and older adult caregivers. Likewise, adult caregivers are younger than older adult caregivers. With regard to the education level, children caregivers have a significantly higher education level than adult's and older adult's, with no meaningful difference between the 2 latest groups. Additionally, children caregivers are mostly women, whereas the presence of male caregivers increases in the adult and older adults group. Conclusions: Thus, the study concludes it is necessary to have differentiated psychosocial care mechanisms, since there are differences between caregivers depending on the age group they take care of.
Keywords: dependency; disabled people; unpaid primary caregivers